Child Growth and Development Monitoring in the Digital Era: A Systematic Review of Mobile and Digital Health Applications in Indonesia - Sofia, Norlaila; Zubaidah, Tien; Hapisah; Noor Adha Aprilea; Rusmilawaty (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2026)
Monitoring child growth and development is essential for improving early childhood health outcomes and preventing stunting; however, monitoring systems in Indonesia remain fragmented and largely focused on anthropometric data. This study synthesizes evidence on digital applications developed between 2020 and 2025 to support child growth and developmental monitoring in Indonesia. Following PRISMA guidelines, 18 studies were identified from national and international databases and appraised using the JBI checklist. The review examined application characteristics, monitoring functions, design quality, user experience, and their contributions to parenting and developmental stimulation. Findings show that most applications prioritize physical growth tracking, while only a minority integrate assessments of cognitive, motor, and socio-emotional development. Thematic synthesis identifies three major gaps: limited incorporation of holistic developmental frameworks, suboptimal interface and interaction quality, and insufficient evidence-based educational content to support sustained caregiver engagement. Although most systems demonstrate high functional performance and methodological quality, interoperability with regional health information networks remains weak, and long-term user engagement is inconsistently documented. Contextual factors influencing these patterns include variability in digital literacy, infrastructural disparities across regions, and the technical challenges of digitizing developmental screening tools. The increasing use of Agile and RAD development approaches indicates potential to improve adaptability, usability, and iterative system refinement. This review underscores the need for integrated, family-centered digital platforms supported by national policy, capacity-building initiatives, and standardized developmental assessment protocols. The synthesized insights provide a foundation for guiding future system development, with interoperability, user-centered design, and equitable access as core principles for strengthening Indonesia’s digital child-health monitoring ecosystem.